2018
DOI: 10.1093/toxsci/kfy199
|View full text |Cite
|
Sign up to set email alerts
|

A Cannabinoid Receptor Type 1 (CB1R) Agonist Enhances the Developmental Neurotoxicity of Acetaminophen (Paracetamol)

Abstract: Acetaminophen (AAP; also known as paracetamol) is the most used and only recommended analgesic and antipyretic among pregnant women and young children. However, recent findings in both humans and rodents suggest a link between developmental exposure to AAP and adverse neurobehavioral effects later in life. We hypothesized that the cannabinoid receptor type 1 (CB1R) may be involved in the developmental neurotoxicity of AAP, owing to its interaction with the endocannabinoid system. Here we test if CB1R agonist W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…This is in line with our hypothesis proposed elsewhere (Viberg et al, 2014; Philippot et al, 2017) where we suggested that PND 10 exposure to AAP (through its metabolite AM404) activate CB 1 R during brain development, which in turn, affects the BDNF–TRKB pathway. Additionally, the negative effect of PND 10 AAP exposure on adult spontaneous behavior and habituation rates was enhanced by simultaneous exposure to CB 1 R agonist WIN 55 212-2 (Philippot et al, 2018), further indicating the critical role of the endocannabinoid system during brain development.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This is in line with our hypothesis proposed elsewhere (Viberg et al, 2014; Philippot et al, 2017) where we suggested that PND 10 exposure to AAP (through its metabolite AM404) activate CB 1 R during brain development, which in turn, affects the BDNF–TRKB pathway. Additionally, the negative effect of PND 10 AAP exposure on adult spontaneous behavior and habituation rates was enhanced by simultaneous exposure to CB 1 R agonist WIN 55 212-2 (Philippot et al, 2018), further indicating the critical role of the endocannabinoid system during brain development.…”
Section: Discussionmentioning
confidence: 96%
“…The transcriptional effect on Trkb following PND 10 exposure to THC is also interesting for the developmental neurotoxic evaluation of AAP; in a previous study, PND 10 exposure to AAP also decreased transcription of Trkb in mice (Philippot et al, 2018). Since both THC and AAP interact with the endocannabinoid system (Bertolini et al, 2006), together with the fact that PND 10 exposure to both these substances affect 1) adult spontaneous behavior and habituation rates and 2) decreased transcript levels of Trkb 24 h after exposure, there is a possibility that both these substances share important events in their respective AOP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Suggested mechanisms relate to modulation of central nervous system inflammation or to paracetamol metabolites, like cannabinoids. Related to this, paracetamol and (9)-tetrahydrocannabinol, but not ibuprofen, resulted in developmental neurotoxicity in a mice model (77,78).…”
Section: Paracetamol Use In Neonates: In Search Of a Better Benefit-rmentioning
confidence: 88%